1993
DOI: 10.1099/00221287-139-6-1235
|View full text |Cite
|
Sign up to set email alerts
|

Genetic organization, sequence and biochemical characterization of recombinant  -xylosidase from Thermoanaerobacterium saccharolyticum strain B6A-RI

Abstract: Endoxylanase (xynA) and P-xylosidase (xynB) genes from Thevmoanaerobacterium saccharofyticum were subcloned from a cosmid clone (pXDM1) to generate pXPH3. The nucleotide sequence of a PstI-Hind111 fragment in pXPH3 that contained xynB revealed an open reading frame (ORF) of 1500 bp encoding a 55 kDa protein.Another open reading frame (ORFl) of unknown function was found 21 bp downstream from the first stop codon of xynB. xynB, ORFl and xynA had the same direction of transcription. xynB from T. saccharolyticum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 34 publications
2
36
0
1
Order By: Relevance
“…When pxylosidase activity is monitored by measuring the amount of pnitrophenol released from p-nitrophenyl p-D-xyloside, the present high transglycosylating activity cannot be detected. The presence of xylotriose in the early stages of the hydrolysis of xylobiose by T. snccharolyticum /i-xylosidase has been detected by TLC (Lee et al, 1993). Transglycosylating activity is a property shared by a number of glycosyl hydrolases such as p-galactosidases, cellulases, P-glucosidases, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When pxylosidase activity is monitored by measuring the amount of pnitrophenol released from p-nitrophenyl p-D-xyloside, the present high transglycosylating activity cannot be detected. The presence of xylotriose in the early stages of the hydrolysis of xylobiose by T. snccharolyticum /i-xylosidase has been detected by TLC (Lee et al, 1993). Transglycosylating activity is a property shared by a number of glycosyl hydrolases such as p-galactosidases, cellulases, P-glucosidases, etc.…”
Section: Resultsmentioning
confidence: 99%
“…p-Nitrophenyl p-D-xylopyranoside was used for this study since earlier experiments had shown it to be the best substrate for the enzyme (Lee and Zeikus, 1993). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative prokaryotic-sequence-like Ϫ10 (TATAGA) and Ϫ35 (TATGTG) promoter sequences as well as a Shine-Dalgarno (GGGGG) site were noted. Screening of protein and nucleic acid data banks revealed that the xylB gene is a homolog of the previously described xynB gene isolated from Thermoanaerobacterium sacharrolyticum (20), the products having 98% amino acid similarity and 91% identity by Bestfit analysis. The differences between the peptide sequences of these two genes are, for the most part, conservative.…”
Section: Gene Isolation and Sequence Analysis (I) Xylbmentioning
confidence: 99%
“…While a number of ␤-xylosidase genes have been isolated from a variety of fungal and mesophilic bacterial sources, few have been isolated from thermophilic bacteria (2,20,23). In contrast to the situation for xylanases and xylosidases, for which microbiological and biochemical information is available, very few genes encoding acetyl xylan esterases have been verified (12,23,24,32), the xynD gene from Pseudomonas fluorescens being the only bacterial representative which has been expressed in Escherichia coli and characterized (12).…”
mentioning
confidence: 99%